1998
DOI: 10.1046/j.1365-2311.1998.00108.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ground cover on spider populations in a table grape vineyard

Abstract: Abstract. 1. Cover crops and/or resident ground vegetation have been used in California vineyards to increase the number of predators and decrease the number of pestiferous herbivores. The most common resident predators in vineyards are spiders (Araneae). Several observational studies suggest that the addition of cover crops results in an increase in spider density and a decrease in insect pest densities.2. To test experimentally the effects of cover crops and/or resident ground vegetation (hereafter collectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
51
3
5

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(62 citation statements)
references
References 23 publications
3
51
3
5
Order By: Relevance
“…The lack of consistency between years may simply be that over all spider density was too low in the Þrst year of study (1993) to be able to statistically separate differences among treatments. In a separate study, T. pacificus density was consistently higher on grapevines with ground covers (Costello and Daane 1998a), but in that study it comprised �40% of the spider community, compared with �7% in the current study. And because T. pacificus density was not signiÞcantly different be tween Cover and Exclusion treatments, it is unlikely that the importance of the ground cover for T. pacificus was in providing additional habitat.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…The lack of consistency between years may simply be that over all spider density was too low in the Þrst year of study (1993) to be able to statistically separate differences among treatments. In a separate study, T. pacificus density was consistently higher on grapevines with ground covers (Costello and Daane 1998a), but in that study it comprised �40% of the spider community, compared with �7% in the current study. And because T. pacificus density was not signiÞcantly different be tween Cover and Exclusion treatments, it is unlikely that the importance of the ground cover for T. pacificus was in providing additional habitat.…”
Section: Discussioncontrasting
confidence: 75%
“…One of our stud ies showed no consistent differences in total spider density on grapevines (where leafhopper nymphs are found) grown with ground cover or not (Costello and Daane 1998a). An alternative hypothesis is the possi ble inßuence of ground covers on grapevine vigor.…”
contrasting
confidence: 54%
“…Overall, the results of this study were consistent with previous findings in perennial systems, which indicated that weed management practices affect groundcover vegetation (Monteiro and Lopes, 2007) and can influence the composition of terrestrial arthropod communities (Altieri and Schmidt, 1985;Costello and Daane, 1998;O'Neal et al, 2005). Thus, incorporating vegetation strips as a part of weed management practices in vineyards, whether using resident vegetation or low-growing cover crop species, can help neutralized the impacts of herbicides on biodiversity of the system.…”
Section: Discussionsupporting
confidence: 89%
“…There are very few studies involving arthropod communities in vineyard, especially those that are classified as ground dwellers, and their roles as natural enemies of vineyard pests (Costello and Daane, 1998;Costello and Daane, 2003). Landis et al (2000) stated that conservation biological control (of crop pests) involves manipulation of the environment to enhance the survival, fecundity, longevity, and behavior of natural enemies to increase their effectiveness.…”
Section: Literature Reviewsmentioning
confidence: 99%
“…Many California growers are also willing to plant cover crops because they protect soil from nutrient and sedi-ment loss in winter storms (Bettiga et al 2006), suppress weeds (Lanini and Bendixen 1992), harbor beneficial arthropods (Costello and Daane 1998), enhance vine mineral nutrition (Patrick et al 2004) and increase soil organic matter (Ingels et al 2005).…”
mentioning
confidence: 99%